PENGARUH RETURN ON ASSET, RETURN ON EQUITY, DEBT TO EQUITY RATIO, UKURAN PERUSAHAAN DAN CURRENT RATIO TERHADAP NILAI PERUSAHAAN (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2015 – 2017) - Elsa Widyawati, 15.05.52.0350; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of Return on Asset, Return on Equity, Debt to Equity Ratio, Company Size and Current Ratio on the firm of value that evolve in manufacturing company at Indonesia Stock Exchange. The population of this research is any type of manufacturing companies that have been registered at Indonesia Stock Exchange on the period of 2015 – 2017. The method used as identifying the data is purposive sampling. The relation and impact within variables are straightly explained by using multiple linear regression analysis method. The result presents that Return on Asset, Return on Equity and the Company Size have a positive significant impact to the firm of value, meanwhile Debt to Equity Ratio and Current Ratio are not significantly affected the firmof value.